Self-selection and Motivations of Emigrants from a Welfare State - Ilpo Kauppinen; Till Nikolka; Panu Poutvaara (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
This report analyzes self-selection and motivations of emigrants from Denmark, one of the richest and most redistributive welfare states in the world. Authors Ilpo Kauppinen (EconPol Europe, VATT Institute for Economic Research), Till Nikolka (EconPol Europe, ifo Institute, LMU Munich) and Panu Poutvaara (EconPol Europe, ifo Institute, LMU Munich) present evidence on how migrants are self-selected with respect to their education, earnings, and unobservable abilities, measured by residual earnings. They document main motivations of emigrants, present evidence on how couples have self-selected into emigration, how couples decided on their emigration and how the partners' labor force participation changed after emigration. Finally, they ask whether emigrants differ from non-migrants in terms of their attitudes towards redistribution.
Keywords: 330